Side-to-side growth discrepancies in children with hemiplegic cerebral palsy: association with function, activity and social participation - Marise Bueno Zonta; Amâncio Ramalho-Júnior; Marilene Puppi; Isac Bruck; Neiva Magdalena; Sandra Regina B. Muzzolon; Arnolfo de Carvalho-Neto; Lúcia H Coutinho dos Santos (Arquivos de Neuro-Psiquiatria)
Objective: Evaluate side-to-side discrepancies in children with hemiplegic cerebral palsy (HCP), and investigate associations of these discrepancies with patients’ age at initiation of physical therapy, motor and cognitive function, and degree of activities and social participation. Method: We obtained eight side-to-side measurements from 24 HCP children with mean age 49.3±5.2 months. Results: Early initiation of physical therapy was associated with lower discrepancy in hand length (p=0.037). Lower foot length discrepancy was associated with lower requirement for caregiver assistance in activities related to mobility. Increased side-to-side discrepancy was associated with reduced wrist extension and increased spasticity. Discrepancy played a larger role in children with hemineglect and in those with right involvement. Conclusion: Increased discrepancy in HCP children was associated with reduced degree of activity/social participation. These results suggest an association between functional use of the extremities and limb growth.